Death of a fool - Marsh, Ngaio, 1895-1982 (Marsh, Ngaio, 1895-1982. Roderick Alleyn, 2014)
The village of South Mardian likes the old ways. This may be 1957, but South M. still features a blacksmith, a village idiot, and an elaborate fertility ritual performed at the winter solstice. There's squabbling, of course, and things come to a head when one of the ritual's main players is found be-headed, everything north of his neck having been neatly lopped off by a ritual sword. Inspector Alleyn does have to contain a certain incredulous amusement at South M.'s fetishistic embrace of the 18th century, but he contains the giggles long enough to name the baddie and return all to the warm embrace of pre-Industrial Britain.